Identification of Two R2R3-MYB Genes Involved in Flavan-3-Ols Biosynthesis as Modulated by Salicylic Acid Through RNA-Seq in Grape Berries (Vitis spp.) - Fengchan Yu; Pengfei Zhai; Wenjing Ge; Runtian Zhou; Shuwen Zan; Jinjun Liang; Pengfei Wen; Yu Gary Gao (Agriculture)
Flavan-3-ols are plant secondary metabolites that play important roles in stress resistance. Our previous studies revealed that salicylic acid (SA) activates R2R3-MYB transcription factors, promoting flavan-3-ol biosynthesis. This study identified two R2R3-MYB genes that exhibited positive responses to both exogenous SA and were probably involved in flavan-3-ol biosynthesis through RNA-sequencing, functional enrichment analysis, and qRT-PCR. The results indicated that the contents of total flavan-3-ols and their monomers, (+)-catechin and (−)-epicatechin, in grape berries after exogenous SA application were substantially increased compared to those in the control. A total of 683 differentially expressed genes in response to exogenous SA treatment were identified using RNA-seq. KEGG analysis revealed enrichment of the ‘flavonoid biosynthesis’ and ‘plant hormone signal transduction’ pathways. A specific module highly associated with flavan-3-ol biosynthesis was identified by constructing a co-expression network. Two candidate genes (VvMYB108B and VvMYB145) likely participating in flavan-3-ol biosynthesis were selected using qRT-PCR. Therefore, these two potential genes that respond to SA and putatively participate in flavan-3-ol biosynthesis were identified for the first time. These results lay a solid basis for a more profound understanding of the molecular regulation of flavan-3-ol biosynthesis in grapes.